EVALUASI PENGEMBANGAN DESA BUDAYA KERTALANGU DENPASAR SEBAGAI DAYA TARIK WISATA - I Made Agus Asta Panca; I Nyoman Darma Putra (JURNAL MASTER PARIWISATA, 2016)
The Kertalangu Cultural Village, located just north of Sanur beach, was established in 2007 and meant to be an alternative tourist attraction in Denpasar. Initially, this cultural village had developed as planned, but later on it faced a phase of decline. This article evaluates the  implementation of Kertalangu Cultural Village development program seen from the aspect of context, input, process and product. Data were collected by interviewing and distributing questionnaires. The total number of respondents was 97, determined using the Slovin formula, with the disproportionate stratified random sampling technique. Data were analyzed by Evaluation Theory, Theory of Sustainable Tourism Development and Tourism Regional Development Theory. The results show that the implementation of Kertalangu Cultural Village development programs is still not running optimally. The constraints that faced are the management is not optimal, the limited budget allocated to the development of tourism potential and the lack of good coordination between the manager and the manager at the Kesiman Kertalangu Village.